Media and information literacy in Colombian teacher education: Insights from Implementing the UNESCO MIL Curriculum - Durán-Becerra, Tomás; Payán-Durán, Luisa; Machuca-Téllez, Gerardo; Castillo Rodríguez, Cristian (Corporación Universitaria Minuto de Dios - UNIMINUTO, 2023)
Colombia has reached a level of maturity concerning the establishment of enabling technologies. Nevertheless, the country’s educational system has yet to achieve consistent and widespread quality across the entire national territory. Evident disparities exist in academic achievements among secondary school students in urban versus rural areas and between the official and nonofficial sectors. However, this study reveals that the country possesses contextual conditions conducive to advancing media and information literacy (MIL). These conditions stem from advancements in technological infrastructure and the alignment of the United Nations Educational, Scientific and Cultural Organization (UNESCO) MIL curriculum learning outcomes for teachers with both the interests and content of the national curriculum and the curricula implemented by the schools studied. This study introduces the initial stages of piloting the UNESCO MIL curriculum across 23 schools in Colombia, marking the initial strides toward developing an MIL policy for the country.
Capítulo completo en acceso abierto que hace parte de la obra Media and information literacy for the public good: UNESCO MILID Yearbook 2023.
Keywords: Alfabetización mediática e informacional; Política; Plan de estudio; Educación; Formación docente; 374.0124; Media and information literacy; MIL policy; MIL curriculum; MIL education; Teacher training; Literacy (Education) — Case Studies; Primary Education; Education and Development; Vocational Training; Media Literacy; Adult Literacy — Research